Atypical Vulvar Mass: Metastatic Vulvar Crohn’s Disease in a Young Female with Rheumatoid Arthritis: A Case Report - Shweta Kanyal; Pauras Mhatre; Kapil Agrawal; Vidhi Mehta; Pooja Kathare (International Journal of Medical Students)
BACKGROUND: Crohn’s disease (CD) is an inflammatory bowel disease that usually manifests in any part of the gastrointestinal tract from the oral cavity to the anus, with well-known extraintestinal presentations such as uveitis, erythema nodosum and arthritis. Rarely, it can also present with metastatic vulvar lesions, a conundrum for the gynecologist and gastroenterologist, owing to its similarity with other granulomatous and dermatological conditions like hidradenitis suppurativa, cellulitis and secondary abscess, making it a diagnostic dilemma.